2022
DOI: 10.1007/s00417-022-05740-4
|View full text |Cite
|
Sign up to set email alerts
|

Meridional ocular magnification after cataract surgery with toric and non-toric intraocular lenses

Abstract: Background Overall ocular magnification (OOM) and meridional ocular magnification (MOM) with consequent image distortions have been widely ignored in modern cataract surgery. The purpose of this study was to investigate OOM and MOM in a general situation with an astigmatic refracting surface. Methods From a large dataset containing biometric measurements (IOLMaster 700) of both eyes of 9734 patients prior to cataract surgery, the equivalent (PIOLeq) and cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Thus, especially for (toric) IOLs with higher refractive power, the prediction of postoperative pseudophakic ACD may make sense 26 . Theoretically, a paraxial vergence calculation can additionally address total and meridional ocular image magnification in addition to just calculating the required lens power to incorporate aniseikonia into the selection of the appropriate IOL combination 27 , 28 . In our case, the cornea was calculated as a thick lens.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, especially for (toric) IOLs with higher refractive power, the prediction of postoperative pseudophakic ACD may make sense 26 . Theoretically, a paraxial vergence calculation can additionally address total and meridional ocular image magnification in addition to just calculating the required lens power to incorporate aniseikonia into the selection of the appropriate IOL combination 27 , 28 . In our case, the cornea was calculated as a thick lens.…”
Section: Discussionmentioning
confidence: 99%
“…1 While monovision options may avoid photic phenomena, disadvantages, such as a loss of binocular summation, asthenopia, aniseikonia, loss of stereopsis, and dissatisfaction with defocus in the myopic eye, may limit this approach in many patients. 2,3 In 2011, Iida et al reported a new mix-and-match technique called "hybrid monovision" for reducing presbyopia after cataract surgery. 4 This approach combines a monofocal IOL in the dominant eye with a MFIOL in the non-dominant eye.…”
Section: Introductionmentioning
confidence: 99%